2010
DOI: 10.1038/gene.2010.39
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association identifies SKIV2L and MYRIP as protective factors for age-related macular degeneration

Abstract: Age-related macular degeneration (AMD) is the leading cause of blindness in the elderly in the developed world. We conducted a genome-wide association study in a series of families enriched for AMD and completed a meta-analysis of this new data with results from reanalysis of an existing study of a late-stage case/control cohort. We tested the top findings for replication in 1 896 cases and 1 866 controls and identified two novel genetic protective factors for AMD. In addition to the CFH (p=2.3×10−64) and ARMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 79 publications
1
49
0
Order By: Relevance
“…Maller et al 2006), (Spencer et al 2007;Seddon et al 2009;Francis et al 2009) Unknown whether these SNPs are associated with AMD due to a functional change in either the C2 or CFB genes, or even both. rs547154 (C2) None (SNP in non-coding region) Maller et al 2006), (Spencer et al 2007;Jakobsdottir et al 2008;Richardson et al 2009;Gibson et al 2010) NB: rs9332739 (C2) in LD with rs4151667 (CFB), and rs547154 (C2) in LD with rs641153 (CFB) rs4151667 (CFB) L9H Maller et al 2006) rs641153 (CFB) R32Q Maller et al 2006), (Spencer et al 2007;Seddon et al 2009;Richardson et al 2009;Kopplin et al 2010) C3 19p13.3-p13.2 rs2230199 R102G (Yates et al 2007;Maller et al 2007;Spencer et al 2008b;Seddon et al 2009;Despriet et al 2009;Park et al 2009;Francis et al 2009;Scholl et al 2009;Chen et al 2010;McKay et al 2010;Gibson et al 2010;Kopplin et al 2010) NB. These two SNPs are in LD with each other rs1047286 P314L (Spencer et al 2008b;Despriet et al 2009;Park et al 2009; …”
Section: The Complement Pathwaysmentioning
confidence: 94%
See 1 more Smart Citation
“…Maller et al 2006), (Spencer et al 2007;Seddon et al 2009;Francis et al 2009) Unknown whether these SNPs are associated with AMD due to a functional change in either the C2 or CFB genes, or even both. rs547154 (C2) None (SNP in non-coding region) Maller et al 2006), (Spencer et al 2007;Jakobsdottir et al 2008;Richardson et al 2009;Gibson et al 2010) NB: rs9332739 (C2) in LD with rs4151667 (CFB), and rs547154 (C2) in LD with rs641153 (CFB) rs4151667 (CFB) L9H Maller et al 2006) rs641153 (CFB) R32Q Maller et al 2006), (Spencer et al 2007;Seddon et al 2009;Richardson et al 2009;Kopplin et al 2010) C3 19p13.3-p13.2 rs2230199 R102G (Yates et al 2007;Maller et al 2007;Spencer et al 2008b;Seddon et al 2009;Despriet et al 2009;Park et al 2009;Francis et al 2009;Scholl et al 2009;Chen et al 2010;McKay et al 2010;Gibson et al 2010;Kopplin et al 2010) NB. These two SNPs are in LD with each other rs1047286 P314L (Spencer et al 2008b;Despriet et al 2009;Park et al 2009; …”
Section: The Complement Pathwaysmentioning
confidence: 94%
“…An intronic variation in a near-by gene, SuperkillerViralicidic Activity 2 (SKIV2L) has also been associated with AMD. This gene is considered to have a role in defence against RNA viruses; however its association with complement is uncertain Kopplin et al 2010).…”
Section: Complement C2 + Complement Factor Bmentioning
confidence: 99%
“…They concluded that variations within SKIV2L might exert a functional effect in AMD. Furthermore, Kopplin et al 34 performed a genome-wide association study (GWAS) in 1896 cases of AMD and 1866 controls and observed a protective effect of an intronic SNP, rs429608 (P ¼ 5.3 3 10 À15 ), to AMD in the SKIV2L gene. In addition, Lee et al 40 and Kondo et al 41 investigated the association between the C2/BF locus and PCV, which is one type of wet AMD (wet AMD includes CNV and PCV); they could not find a significant association between the previously reported SNPs and PCV in Singapore Chinese and Japanese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Six of these 13 SNPS, including rs9332739, rs547154, rs4151667, rs641153, rs760070, and rs429608, were reported in previous studies to be associated with AMD. 24,33,34 The other seven haplotypetagging SNPs were obtained from the C2-BF-RD RNA-binding protein (RDBP)-SKIV2L-serine/threonine kinase 19 (STK19) region spanning 46 kb (Chr6: 32,001,000-32,047,000) in the Han Chinese population in Beijing, China (CHB), drawn from the HapMap database (HapMap Public Release #27 on Genome Browser, http://hapmap.ncbi.nlm.nih.gov/). Several of these SNPs had been genotyped in some of the samples in our previous study.…”
Section: Selection Of Snpsmentioning
confidence: 99%
See 1 more Smart Citation